Measurement of torque generated during intracanal instrumentation in vivo. (4th December 2018) - Gambarini, G.; Seracchiani, M.; Piasecki, L.; Valenti Obino, F.; Galli, M.; Di Nardo, D.; Testarelli, L.
Abstract: Aim: To compare two different clinical techniques when using endodontic rotary instruments by monitoring the torque in vivo . Methodology: Ten single‐rooted maxillary anterior teeth were prepared by an endodontist using size 25, .06 taper TF rotary instruments (KerrEndo, Orange, CA, USA). All instruments were rotated at 500 rpm with maximum torque set at 2.5 N cm using an endodontic motor (Kavo, Biberach, Germany), which automatically recorded the torque values every 1/10 of a second. Instruments were used with two modi operandi : (i) Inward action: short‐length intermittent progression with slight apical pressure aiming to reach the working length (also known as pecking motion), followed by (ii) Outward action: lateral brushing action selectively directed to address the canal circumference whilst removing instruments in the coronal direction. The mean, maximum and accumulated torque values were recorded and analysed statistically ( t ‐test and Wilcoxon test) with a significance level set at 5%. None of the recorded values exceeded the selected torque limit. Results: A significant difference between inward and outward actions was found regarding the evaluated parameters ( P < 0.05). The outward action (brushing) was significantly safer (requiring less torque) compared to the inward action (pecking). Conclusions: Torque measurements during in vivo instrumentation provided useful information regarding the techniques evaluated. Although the torque limit was not reached by any of the two actions, the technique impacted significantly on the torque applied to the instrument.